2010
DOI: 10.1186/1476-4598-9-99
|View full text |Cite
|
Sign up to set email alerts
|

Differential chemosensitization of P-glycoprotein overexpressing K562/Adr cells by withaferin A and Siamois polyphenols

Abstract: BackgroundMultidrug resistance (MDR) is a major obstacle in cancer treatment and is often the result of overexpression of the drug efflux protein, P-glycoprotein (P-gp), as a consequence of hyperactivation of NFκB, AP1 and Nrf2 transcription factors. In addition to effluxing chemotherapeutic drugs, P-gp also plays a specific role in blocking caspase-dependent apoptotic pathways. One feature that cytotoxic treatments of cancer have in common is activation of the transcription factor NFκB, which regulates inflam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
39
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 65 publications
(42 citation statements)
references
References 101 publications
2
39
0
1
Order By: Relevance
“…In order to further elucidate the underlying mechanisms of ROS-induced MDR, immunofluorescence staining was performed to examine several transcriptional factors in close relationship with oxidative stress, including Nrf2, NF- κ B-p65, and HIF-1 α , which were also widely reported as regulators of efflux transporter like P-gp and MRP1 [2124]. Our results showed that Nrf2, NF- κ B-p65, and HIF-1 α were found to be highly expressed in MCF-7/ROS cells compared to control MCF-7 cells.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to further elucidate the underlying mechanisms of ROS-induced MDR, immunofluorescence staining was performed to examine several transcriptional factors in close relationship with oxidative stress, including Nrf2, NF- κ B-p65, and HIF-1 α , which were also widely reported as regulators of efflux transporter like P-gp and MRP1 [2124]. Our results showed that Nrf2, NF- κ B-p65, and HIF-1 α were found to be highly expressed in MCF-7/ROS cells compared to control MCF-7 cells.…”
Section: Resultsmentioning
confidence: 99%
“…Firstly, overexpressions of functional P-gp and MRP1, which are classic efflux mechanisms of anticancer drugs and correlate broadly with negative treatment response [44], were found in MCF-7 cells after long-term treatment with both H 2 O 2 and GSH. Secondly, the transcriptional factors of efflux transporter, such as Nrf2, NF- κ B, and HIF-1 α [2124], were also upregulated in MCF-7/ROS cells. Importantly, the elevated levels of Nrf2 and HIF-1 α were mainly localized in the nuclei of MCF-7/ROS cells, which suggested them in activation.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the strategy of using an ROS-generating agent to enhance cytotoxicity may not be generally applied to all cases. For resistant cells with a high antioxidant capacity, such strategies enhance cell survival and impair cellular responses to anticancer therapy (Suttana et al, 2010: Ding et al, 2015. Molecular event triggers in these cells require further study to better understand the mechanism underlying the effect of IronQ, although the present study provides preliminary experimental evidence of the efficiency of IronQ to sensitize cancer cells to radiotherapy.…”
Section: Discussionmentioning
confidence: 84%
“…Also, chronic exposure to chemotherapeutic agents may epigenetically reprogram cancer cell metabolism and gene expression and trigger chemoresistance (Blair et al, 2011;Kujjo et al, 2011;S. V. Sharma et al, 2010;W. Suttana et al, 2010).…”
Section: Cancer-inflammation Cancer Metabolism and Epimutations: Caumentioning
confidence: 99%
“…Iliopoulos et al, 2009;S. Maeda et al, 2009;Min et al, 2010;Naugler & Karin, 2008;W. Suttana et al, 2010;Yu et al, 2009).…”
Section: Cancer-inflammation Cancer Metabolism and Epimutations: Cauunclassified